(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Today, the success or failure of organizations depends to possess the wisdom of their managers promised that the key to organizational success of the business environment, making the right decisions, and create the ability to work and think towards discrimination of products and services the organization . Seek this research to investigation the relationship between the wisdom management and differentiation strategy for service operations . It was a test of that relationship in light of the results of the analysis of the data collected through the questionnaire distributed on a sample from (98) Director Mangers, head of department and head of division in the General Establishment of Civil Aviation . The research used descriptive statistics such as (Mean , Standard Deviation ) in determining the strength of variables , and non-parametric deduction statistics such as ( spearman correlation coefficient ) to test the hypotheses . The results show Significant effect & correlation relationship between the two variables due to their dimensions . So , it leads to the possession of the leaders of vision and insight, experience and competence in the work, will contribute to the putting of astrategy plan for researched the organization levelThe research provided some ecommendations